Pollution Bio- indicators In Al-Diwania River A1- (^a?lisia Province / Iraq (Baghdad Science Journal, 2004)
Benthic invertebrates were used as bio- indicators to evaluate the pollution in -Diwania River . Five stations were selected for this purpose , extending from A1 -?? rtream to A1- Sadeer District downstream . The percentage of?ct uP?str?^ ? ?, oligochaeta to total benthic invertebrates were calculated . The population density of evaluation. 'I'he results Were ??? Tubificid worms without hair ehaetae was ©iso used IOBS(01igochaete Index of Sediment Bioindicati©n ), TUSP ? presented as indices Io (Tubificidae Species Percentage ) & degree of pollution Eo . IT was noticed that the 0 in??37.17 percentage of ©lig©chaeta to the total benthic invertebrates ranged between to 60.685 in station 3 , while the percentage ©f Tubificid w©rms t© ©ther ? stati©n oligochaeta ranged from 32% in station 2 to 74.17% in station 3.Io values ranged between 21.3 in station 3 to 22.3 in station I , while lobs index showed a higher value 7.62 in station 3 and lawer value 2.43 in station 3 .the higher value of TUSP index was 32,5 in stati©n 5 and the lawer valus was 15.9 in station 1 . Pollution degree F1 ( percentage ©f Tubificidae without hair M/gg& ? was rec©rded in stati©n 5-96 respectively ) and degree E in station 3,4&5 (percentage of Tubificidae & ?4-? without hair ehaetae was 15.95 , 15.95 & 16.16 respectively ). According to these results, stati©n 1 & 2 may be regarded as free fr©m p©lluti©n , while the other stations. were considered as slightly p©lluted